2009
DOI: 10.1111/j.1758-0854.2009.01019.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Deterrent Pictures Effective? The Impact of Warning Labels on Cognitive Dissonance in Smokers

Abstract: An experiment was conducted to investigate the impact of cigarette warning labels on cognitive dissonance in smokers. Smokers' and non‐smokers' risk perceptions with regard to smoking‐related diseases were measured with ratings as well as with response latencies before and after presentation of warning labels. Results indicated an influence of warning labels on smokers' ratings, revealing cognitive dissonance reducing strategies after confrontation with warning labels. Response latencies showed an impact of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 45 publications
0
53
0
1
Order By: Relevance
“…This may in part be due to the common difficulty of transforming intentions into actual behavior (Webb & Sheeran, 2006). Moreover, experimental studies have presented evidence that in some cases, negative or threatening information may in fact have opposite effects, such as defensive responses (Glock & Kneer, 2009), psychological reactance (Erceg-Hurn & Steed, 2011), or even completely adverse effects, such as a reduced risk perception (Myers, 2014). Pure knowledge about dangers and risk, as it is often provided by prevention programs or warning labels, was often found to have very little predictive value for actual risk behavior (Rosendahl, Galanti, Gilljam, & Ahlbom, 2005).…”
mentioning
confidence: 97%
“…This may in part be due to the common difficulty of transforming intentions into actual behavior (Webb & Sheeran, 2006). Moreover, experimental studies have presented evidence that in some cases, negative or threatening information may in fact have opposite effects, such as defensive responses (Glock & Kneer, 2009), psychological reactance (Erceg-Hurn & Steed, 2011), or even completely adverse effects, such as a reduced risk perception (Myers, 2014). Pure knowledge about dangers and risk, as it is often provided by prevention programs or warning labels, was often found to have very little predictive value for actual risk behavior (Rosendahl, Galanti, Gilljam, & Ahlbom, 2005).…”
mentioning
confidence: 97%
“…Sigara paketleri üzerindeki saðlýk uyarýlarýnýn, psikolojik tepkiselliðe neden olmanýn yaný sýra, sigara içenler üzerinde biliþsel çeliþkiye yol açabile-ceði de ileri sürülmektedir (34). Biliþsel Çeliþki Kuramýna göre (2) bireyler ayný anda birbiri ile tutarsýz iki biliþsel temsile sahip olduklarýnda 'biliþsel çeliþki' olarak adlandýrýlan psikolojik bir durum deneyimlerler.…”
Section: Rahatsýz Edici Sigara Uyarýlarýna Yönelik Savunmacý Tepkilerunclassified
“…For example, since 2003, warning labels have been shown on cigarette packs, and alcohol commercials in The Netherlands are required to state that responsible alcohol consumption is advised. This distinction is important as, for instance, Glock and Kneer (2009) found that smokers, compared to non-smokers, were realistic about their higher chance of contracting a smoking-related illness (e.g. lung cancer).…”
Section: Theoretical Backgroundmentioning
confidence: 99%